2011
DOI: 10.1016/j.neuron.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Modes of AMPA Receptor Suppression at Developing Synapses by GluN2A and GluN2B: Single-Cell NMDA Receptor Subunit Deletion In Vivo

Abstract: Summary During development there is an activity-dependent switch in synaptic NMDA receptor subunit composition from predominantly GluN2B to GluN2A, though the precise role of this switch remains unknown. By deleting GluN2 subunits in single neurons during synaptogenesis, we find both GluN2B and GluN2A suppress AMPA receptor expression, albeit by distinct means. Similar to GluN1, GluN2B deletion increases the number of functional synapses, while GluN2A deletion increases the strength of unitary connections with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
294
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(326 citation statements)
references
References 90 publications
(163 reference statements)
26
294
5
1
Order By: Relevance
“…Most studies support the model in which activation of NMDARs promotes the recruitment of AMPARs to immature synapses (25,43). However, single-cell deletion of NMDARs in the hippocampus led to an up-regulation of AMPAR-EPSCs in CA1 neurons by increasing the number of functional synapses (29,44). This is in contrast with our results in the thalamus, in which deletion of NMDARs blocked the upregulation of AMPARs at the synapse.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Most studies support the model in which activation of NMDARs promotes the recruitment of AMPARs to immature synapses (25,43). However, single-cell deletion of NMDARs in the hippocampus led to an up-regulation of AMPAR-EPSCs in CA1 neurons by increasing the number of functional synapses (29,44). This is in contrast with our results in the thalamus, in which deletion of NMDARs blocked the upregulation of AMPARs at the synapse.…”
Section: Discussionsupporting
confidence: 65%
“…However, such effect was not observed in another study that used single-cell deletion of GluN2B or GluN1 in the hippocampus (29). One possibility for this discrepancy is the difference in the time of deletion between these two studies, as the former used the embryonic nestin Cre driver (39), whereas the latter used viral transfection in newborn mice for Cre expression (29). However, both studies found significant reductions in spine density in hippocampal neurons without GluN2B, which is inconsistent with a role of the receptor in pruning of synapses.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Specifically, embryonically generated neurons face an environment with sparse synaptic activity. It was shown that under these circumstances GluN2B-containing NMDARs negatively regulate the incorporation of synaptic AMPA receptors (AMPARs) (Hall et al, 2007;Adesnik et al, 2008;Gray et al, 2011). In contrast to cortical development, adult-born neurons integrate into networks characterized by strong and concerted synaptic activity.…”
Section: Introductionmentioning
confidence: 99%